An overview on recent approaches for vehicle routing problems with loading constraints - Pinto, Telmo (2011)
Most of the approaches developed for vehicle routing problems require only that the total weight or volume of the load does not exceed the capacity of the vehicles. For many real distribution applications, these approaches are not adequate, since they lead most of the time to suboptimal or even infeasible solutions. Here, we focus on those applications where the loading of the vehicles is a di cult issue that must be considered explicitly when planning the routes. The vehicle routing problem with loading constraints is NP-hard since it combines two well-known and di cult problems, namely the vehicle routing problem with the packing problem. The study of these problems has motivated an increasing interest and approaches in recent times. The vast majority of the approaches described in the literature focus on heuristic approaches. They address di erent variants of the problem. Developing exact approaches and strong models for these problems remains a true challenge. In this paper, we provide an updated survey on recent contributions on that field.